Prevalence of cardiac autonomic dysfunction in patients with metabolic syndrome: a cross-sectional, observational study - Lohakare, Akash C.; Mehta, Pawan; Singh, Shuchi (International Journal of Research in Medical Sciences, 2019)
Background: Cardiovascular autonomic neuropathy (CAN) is a distinguished disorder associated with diabetes mellitus and metabolic syndrome. The pathogenesis of CAN in patients with metabolic syndrome still remains unclear. This study was undertaken to assess the prevalence of cardiac autonomic dysfunction in patients with metabolic syndrome and to correlate different parameters of metabolic syndrome with cardiac autonomic dysfunction. Methods: In this cross-sectional observational study, total 100 consecutive cases meeting the inclusion criteria and attending the Department of Medicine in Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi were enrolled. 50 subjects who satisfied the IDF criteria of metabolic syndrome were taken as cases and remaining 50 subjects (age and gender matched) who did not satisfy the IDF criteria were taken as controls. Comparison of categorical variables was made using chi-square or Fisher’s exact test. P-value <0.05 was considered as statistically significant. Results: Majority of study population (i.e., 42%) belonged to the age group of 41-50 years. Overall prevalence of cardiac autonomic dysfunction (CAD) was 25%. Prevalence of CAD among cases and controls was 38% and 12%, respectively. Overall distribution of various parameters like waist circumference, fasting blood glucose, blood pressure, HDL-C and serum triglycerides was assessed in all subjects with respect to CAD. Statistically significant association of these parameters was seen with CAD (p-value ≤0.01). Conclusions: In this study, strong association was found between CAD and central obesity, impaired fasting glucose, high blood pressure and dyslipidemia. Thus, the metabolic disorders are good predictors of CAD.